Pemberdayaan Masyarakat melalui Pelatihan Analisis Fundamental Saham bagi Investor Pemula - Zunaidi, Putra Eka; Rini, Hesty Prima (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Novice investors tend to rely on trends and informal recommendations when making stock investment decisions, which motivated this community service activity. The purpose of this activity was to improve novice investors’ understanding of how to apply fundamental stock analysis in making long-term investment decisions. Experiential-based training, also known as experiential learning, was implemented through material delivery, interactive discussions, and assignments involving simple analysis of company financial statements. The evaluation process was conducted through observation, reflective discussions, and assessment of participants’ task results. The results show that most participants gained a better understanding of basic capital market concepts, key financial ratios, and how to perform initial financial statement analysis. This activity also encouraged participants to change their way of thinking and adopt more data-driven and rational investment behavior. These results indicate that novice investors require fundamental analysis training to develop a long-term investment perspective.